The Thriving Women Entrepreneurs in Tamil Nadu : Motivational Factors - Vijay Anand, V.; Panchanatham, N. (Prabandhan: Indian Journal of Management, 2011)
The aim of the present study is to test the status of Women Entrepreneurs in India with reference to selective cities in Tamil Nadu. This study was carried out as the role of women entrepreneurs has gained significance in today’s environment. The present study is based on the women entrepreneurs in and around Trichy and Thanjavur. Women, who succeed as entrepreneurs, are risk taking personalities. The women entrepreneurs have their own identity in the world of entrepreneurship. Most of them are capable of fully identifying themselves in their new economic role in society. In this research, stratified sampling technique was used. A detailed questionnaire bringing out the various aspects of the study was first prepared and tested. In this research, 60 successful women entrepreneurs were interviewed. The sample was selected from two towns, Trichy and Thanjavur. The sample selection was as under: Trichy - 60% and Thanjavur - 40% . This break up was due to the fact that there was a greater concentration of available successful women entrepreneurs in Trichy when compared to Thanjavur. The study has highlighted many factors that have motivated women entrepreneurs in starting an entrepreneurial career. Success has been seen mostly among the mid thirty and early forty age group. The government schemes, incentives and subsidies have stimulated and provided support measures to women entrepreneurs in and around the city. In this research, one of the findings was that while a majority of women came from a family business, as a core background, and they were mostly married into business families. The business environment seems to have prepared them mentally, thereby facilitating their entry into business. Help and guidance was also available within the family in case of any business problems.